2015
DOI: 10.1007/s00384-015-2314-7
|View full text |Cite
|
Sign up to set email alerts
|

Tailored prolapse surgery for the treatment of hemorrhoids with a new dedicated device: TST Starr plus

Abstract: TST Starr plus seems to be safe and effective for a tailored transanal stapled surgery for the treatment of III-IV degree hemorrhoidal prolapse. The new conformation and innovative technology of the stapler seems to reduce some postoperative complications and recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…This device could reduce the recurrence rate through the possibility of more tissue resection basis of the entity of the prolapse 23 . Naldini, et al reported that 1.9% prolapsed recurrence after operation in a median follow-up of 14.5 months 40 . This series also showed no occurrence of anorectal stricture and it could be due to the larger diameter of stapler (36 mm) than PPH (33 mm) or DST (33 mm).…”
Section: Discussionmentioning
confidence: 99%
“…This device could reduce the recurrence rate through the possibility of more tissue resection basis of the entity of the prolapse 23 . Naldini, et al reported that 1.9% prolapsed recurrence after operation in a median follow-up of 14.5 months 40 . This series also showed no occurrence of anorectal stricture and it could be due to the larger diameter of stapler (36 mm) than PPH (33 mm) or DST (33 mm).…”
Section: Discussionmentioning
confidence: 99%
“…There are different types of surgical procedure to treat hemorrhoids according to the symptoms and anatomical presentation. In fact, nowadays there is an open debate about the right operation to perform focusing on a tailored treatment of hemorrhoids [3]. One of the most spread procedure for circumferential prolapse is stapled hemorrhoidopexy.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported an higher recurrence rate than the conventional hemorrhoidectomy [1] even if the patients usually refer an high grade of satisfaction. It is also characterized by low postoperative pain, shorter hospital stay and faster return to work [3].…”
Section: Discussionmentioning
confidence: 99%
“…Although the circular stapled hemorrhoidopexy was also based on the above theory, because of complications such as urgency [15] and anal stenosis [16], surgeons are often reluctant to use PPH. Recent studies have proven the merits of TST, treating prolapsing hemorrhoids without any significant risk [1, 3, 6, 10]. Therefore, TST can be used widely.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhoids were classified into the following stages [9]: (I) anal cushions protruding into the anal canal but maintaining at the proper level, (II) prolapse with bowel movements but with spontaneous reduction, (III) prolapse with bowel movements but requiring manual reduction, and (IV) prolapse but not reducible. Patients with chronic fissure, acute thrombosis, fixed fibrous external hemorrhoids, abscess, benign rectal disease, colorectal carcinoma, anal strictures, and severe primary diseases were not included in the study [10]. HIV-infected patients were selected on the basis of hemorrhoids being their only perianal disease.…”
Section: Methodsmentioning
confidence: 99%